2015
DOI: 10.1097/mao.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration Process of Fungiform Taste Buds After Severing the Human Chorda Tympani Nerve—Observation by Confocal Laser Scanning Microscopy

Abstract: Confocal laser scanning microscopy was useful for clarifying the degeneration process of fungiform taste buds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In the PS group, many subjects with a severed CTN were included. After the CTN was severed, all taste buds had degenerated and disappeared 50 days after surgery (21). In the present study, regenerated taste buds were detected using confocal laser scanning microscopy in 40% of the patients with a severed nerve.…”
Section: Discussionsupporting
confidence: 49%
“…In the PS group, many subjects with a severed CTN were included. After the CTN was severed, all taste buds had degenerated and disappeared 50 days after surgery (21). In the present study, regenerated taste buds were detected using confocal laser scanning microscopy in 40% of the patients with a severed nerve.…”
Section: Discussionsupporting
confidence: 49%
“…13 Recently, the degeneration process of fungiform taste buds after severing the human CTN has been reported using confocal laser microscopy. 6 In 7 patients with a severed CTN, taste buds had completely disappeared at around 50 days on average after surgery. Further observation of the postoperative course of these patients will make it possible to elucidate when the taste buds regenerate and whether the number of regenerated taste buds continuously increases for 1 to 2 years after surgery.…”
Section: Introductionmentioning
confidence: 93%
“…These 7 patients were the same as in our previous report in whom the degeneration process of fungiform taste buds was clarified after severing the CTN. 6 In this study, their FP were periodically observed by a confocal laser scanning microscope until 12 to 24 months after surgery. However, the 7 patients were not overlapped with those in other reports on the regeneration of fungiform taste buds.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations